SPECIES COMPOSITION, DISTRIBUTION AND BIOMASS OF SEAWEEDS AT DUNG QUAT ECONOMIC ZONE, QUANG NGAI PROVINCE, VIETNAM - Ca, Vu Thanh; Hieu, Pham Van; Dinh, Mai Kien; Tien, Dam Duc (Vietnam Journal of Marine Science and Technology, 2014)
Dung Quat economic zone is a major industrial zone in Vietnam. It belongs to Quang Ngai province in Central Vietnam. Until now, there have been few studies on seaweeds at Dung Quat. This article presents results of two field surveys, conducted in February, 2012 and September, 2012 under the research project “Surveying and assessing status of biodiversity in the coasts of Dung Quat economic zone (including expanded area), for the proposal mitigation measures of environmental impacts on biodiversity”. It was found that at the Dung Quat economic area, there are totally 112 seaweed species. Among them, 56 species are Rhodophytes, 27 Chlorophytes, 18 Ochrophytes (Phaeophytes) and 11 Cyanobacteriophytes. The species Scinaia okamurae (Setchell.) Huisman is recorded for the first time in Viet Nam . Number of species at surveyed transects I to VIII varies from 5 species/transect to 61 species/transect and in average 33 species/transect. The Sorensen index varies from 0.00 to 0.667, and in average 0.243. For the depth distribution, among 112 seaweed species, there are 103 species found in the intertidal zone and 82 species found in the subtidal zone (among them, there are 73 species found both in the intertidal and subtidal zones). The majority of species distribute in the mid-tidal zone to a depth of 5m below chart datum. The algal flora nature at Dung Quat economic area is tropical with the ratio C = 4.611. For the biomass, highest are species Sargassum polycystum and Spathoglossum vietnamense; the lowest biomass is species Amphiroa dilatata . There are two valuable and rare species inscribed in the Red data book of Viet Nam as Hypnea cornuta and Kappaphycus cottonii.